Prioritizing Multidimensional Interdependent Factors Influencing COVID‐19 Risk - Qazi, Abroon; Simsekler, Mecit Can Emre; Gaudenzi, Barbara (Risk analysis, 2022)
COVID‐19 has significantly affected various industries and domains worldwide. Since such pandemics are considered as rare events, risks associated with pandemics are generally managed through reactive approaches, which involve seeking more information about the severity of the pandemic over time and adopting suitable strategies accordingly. However, policy‐makers at a national level must devise proactive strategies to minimize the harmful impacts of such pandemics. In this article, we use a country‐level data‐set related to humanitarian crises and disasters to explore critical factors influencing COVID‐19 related hazard and exposure, vulnerability, lack of coping capacity, and the overall risk for individual countries. The main contribution is to establish the relative importance of multidimensional factors associated with COVID‐19 risk in a probabilistic network setting. This study provides unique insights to policy‐makers regarding the identification of critical factors influencing COVID‐19 risk and their relative importance in a network setting.